Prospek HKI Sebagai Agunan Perbankan Indonesia - Ariesta, I Putu Agus Suarsana (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2023)
Increased trading activity is a result of globalization which makes the world a single market where standardization is needed in the economic sector, while the need for capital is often met by the banking sector where credit is one of the favorite facilities. Some of the conditions that must be met in the process of applying for credit, one of which is a guarantee. Legal objects used as collateral in Civil Law are known as goods or objects. IPR are material assets that have commercial value and are included in the category of intangible objects. This research has two formulations of the problem, namely what is the legal basis for IPR can be used as collateral in banking, and whether banks in Indonesia have accepted IPR as collateral. The State of Indonesia has ratified the Trade Related Aspect Intellectual Property Right through Law Number 7 of 1994. Legally IPR can be used as collateral, but until now the banking sector in Indonesia has not accepted IPR as collateral and it is hoped that in the future IPR can be used as collateral in loans issued by banks.